Human FcRn expression and Type I Interferon signaling control Echovirus 11 pathogenesis in mice. - Alexandra I Wells; Kalena A Grimes; Kenneth Kim; Emilie Branche; Christopher J Bakkenist; William H DePas; Sujan Shresta; Carolyn B Coyne (PLoS Pathogens)
Neonatal echovirus infections are characterized by severe hepatitis and neurological complications that can be fatal. Here, we show that expression of the human homologue of the neonatal Fc receptor (hFcRn), the primary receptor for echoviruses, and ablation of type I interferon (IFN) signaling are key host determinants involved in echovirus pathogenesis. We show that expression of hFcRn alone is insufficient to confer susceptibility to echovirus infections in mice. However, expression of hFcRn in mice deficient in type I interferon (IFN) signaling, hFcRn-IFNAR-/-, recapitulate the echovirus pathogenesis observed in humans. Luminex-based multianalyte profiling from E11 infected hFcRn-IFNAR-/- mice revealed a robust systemic immune response to infection, including the induction of type I IFNs. Furthermore, similar to the severe hepatitis observed in humans, E11 infection in hFcRn-IFNAR-/- mice caused profound liver damage. Our findings define the host factors involved in echovirus pathogenesis and establish in vivo models that recapitulate echovirus disease in humans.